Kepastian Hukum Penerapan Ketentuan Pasal 13 Ayat (4) P3b terhadap Transaksi Pengalihan Saham dalam Rangka Reorganisasi oleh Wajib Pajak Singapura di Indonesia - Syafari, Herdin; Ardiansyah, Ardiansyah (Postulat, 2026)
The increase in foreign investment from Singapore to Indonesia often involves corporate restructuring such as mergers, acquisitions, or spin-offs that have implications for cross-border tax obligations. Based on domestic law, every transfer of shares is basically an object of income tax. However, Article 13 paragraph (4) of the Indonesia-Singapore P3B provides an exception for transactions carried out in the context of reorganization, so that the profits from the transfer of shares are not taxed in the source country. The main problem in this study is about the regulation and legal certainty regarding the transfer of shares in the context of reorganization as stipulated in Article 13 paragraph (4) of the Indonesia-Singapore P3B. This study uses a normative legal method with two approaches, namely a legislative approach and a conceptual approach to examine the doctrine of international tax law and the principle of substance over form. Data sources were obtained from primary, secondary, and tertiary legal materials through literature studies which were then analyzed descriptively analytically. The results of the study show that Article 13 paragraph (4) of the Indonesia-Singapore P3B normatively provides legal protection for taxpayers who reorganize without the purpose of tax avoidance. However, in implemention, this provision still faces obstacles in proving the economic substance of transactions due to the absence of an explicit definition of "reorganization" in P3B. Therefore, the application of the substance over form principle is essential to ensure that the reorganization is carried out with legitimate business objectives. Scientifically, this research contributes to strengthening the understanding of the relationship between international tax law and legal certainty in the context of P3B, as well as providing normative recommendations for the establishment of technical guidelines that can clarify the criteria for cross-border reorganization so as not to cause tax disputes and uncertainty for foreign investors.